Effective Ayurvedic Management of Madatyaya (Alcohol Withdrawal Symptoms) (AYUSHDHARA, 2024)
Abruptly reducing or quitting alcohol use is risky for heavy drinkers. Symptoms such as mild to moderate tremors, anxiety, irritation, confusion, delirium, tremors, and seizures are among the worst withdrawal symptoms. The cause of these symptoms lies in the changes that alcohol produces in brain activity, leading to an overabundance of neuronal activity when there is no more alcohol. Ayurveda offers a comprehensive approach that considers not only the body but also the mind. Acharya described Madya as having characteristics that are the opposite of Ojas. Our classics provide a broad explanation of the term "Madatyaya”. This case study describes how to effectively manage the symptoms of alcohol withdrawal using Ayurvedic treatment methods. Clinical Finding: The patient suffered from tremors, nausea/vomiting, anxiety, agitation, headache, disorientation, insomnia, and sweating. Diagnosis: Clinical assessment was done by using the CIWA-Ar scale. Intervention: We initiated treatment with Shanshamana Aushadh (Avipattikar Churna, Ashwagandharishta, Kharjuradi manth, etc) and performed Shirodhara using Bhramhi tail and Til tail. Outcome: Patient showed complete improvement. SGOT, SGPT levels became normal. Conclusion: Ayurvedic treatment of alcohol withdrawal symptoms shows satisfactory clinical result in the patient.